Sharia Banking Efficiency Analysis: ASEAN Countries Comparation - Nailah (Review on Islamic Accounting, 2021)
This study aims to analyze the comparative efficiency of Islamic banks in ASEAN. This study also investigates the reasons for inefficiency and provide suggestions for inefficient banks to improve their efficiency. The study measures and analyzes the pure technical efficiency (PTE), scales efficiency (SE) and technical efficiency (TE) scores of 26 Islamic banks from 4 different countries in ASEAN between 2013 and 2018. Data Envelopment Analysis (DEA), which is a non-parametric method was used. The results indicate that the average for six years of technical efficiency (TE) in the selected Islamic bank is 62,5%. Then for their pure technical efficiency (PTE) and scales efficiency (SE) higher than TE and the scores at 71% and 88%. This paper compares the efficiency of a sample of Islamic banks in 4 countries of ASEAN in very recent years and identifies the most and least efficient banks. It also includes benchmarks for interest-free banks and offers suggestions for improvement.